Excluding Gastroduodenal Artery Pseudoaneurysm from Circulation with Stent-Graft - V. V. Plechev; O. V. Galimov; I. I. Galimov; A. R. Titov; V. Sh. Ishmetov; A. F. Nagaev; T. R. Ibragimov; S. I. Blagodarov; A. R. Gilemkhanov; R. E. Abdrakhmanov; K. I. Zavialov; I. F. Sultanov; et al. (Креативная хирургия и онкология, 2019)
Introduction. Aneurysms of visceral arteries in the abdominal cavity are very rare. Often aneurysms of branches of the abdominal aorta are an incidental finding as patients seldom present obvious clinical signs or pathological changes in the organ supplied by the artery involved. The incidence of aneurysms of branches connecting the celiac trunk and the upper mesenteric artery amounts to 3.5% of all the cases of aneurysms of abdominal aorta arteries, mostly the gastroduodenal artery. This paper presents a case of minimally invasive treatment of gastroduodenal artery pseudoaneurysm at the BSMU Clinic.Materials and methods. Patient K, a 47-year-old female, was admitted for emergency treatment at the Bashkir State Medical University Clinic in May 2019. The patient’s complaints included feeling weak, black stool for seven days prior, faintness and epigastric pain.Results and discussions. Instrumental examination and angiography data demonstrated that the size of the pseudoaneurysm has increased 2.5 times and reached 65×45 mm; the clinical picture led to the conclusion that the aneurysm was ready to rupture and that there was an immediate need to stop the blood flow to the gastroduodenal artery pseudoaneurysm.Conclusion. The range of currently available image-guided surgical procedures makes it possible to perform adequate embolization of pathological structures such as artery aneurysms.